22 Volumetric MRI; A Potential Outcome Measure of Muscle Reinnervation. (4th May 2021) - Wilcox, M; Canas, L D S; Hargunani, R; Tidswell, T; Phillips, J; Modat, M; Ourselin, S; Quick, T
Abstract: Introduction: Improved outcome measures of muscle reinnervation would facilitate clinical translation of new therapies which hope to enhance human peripheral nerve repair. Valid outcome measures should be receptive to the biological process of muscle reinnervation and correlate with clinical assessments of muscular function. This study investigated the responsiveness of volumetric MRI to the biological process of muscle reinnervation and its relationship with clinical indices of muscular function. Method: Twenty-five patients who underwent nerve transfer to reinnervate elbow flexor muscles were followed-up at a median time of 258 days (-86 to 1698 days) post-operatively for a mean of two (one to three) volumetric MRI assessments. Medical Research Council (MRC) grade, peak volitional force (PVF), muscular fatigue, co-contraction and Stanmore Percentage of Normal Elbow Assessment (SPONEA) was also measured at each appointment. The responsiveness of each parameter was compared using Pearson or Spearman correlation as appropriate. Results: Elbow flexor muscle volume per unit BMI demonstrated responsiveness to the biological process of muscle reinnervation (R 2 =0.73, p < 0.001) and correlated with patient reported impairments of reinnervated muscle; co-contraction (R 2 =0.63, p = 0.02) and muscle fatigue (R 2 =0.64, p = 0.04). Conclusions: Volumetric MRI may is an excellent candidate as an outcome measure of muscle reinnervation.